The Picture of Knowledge and Attitudes in Facing with Dysmenorrhe on Faculty Of Medicine Krida Wacana Christian Uniersity Students - Reni Oktavina; Liauw Djai Yen; Doddy Fernando PG; Weldhia Anggun Pramesti (Jurnal MedScientiae, 2023)
Dysmenorrhea is one of health problems that commonly found on teenage girls with a percentage almost more than 50% all around the world. This conditions could caused a pain that bothers through day and day activites, thus decreasing the productivities of each individuals. Knowledge and attitude that are right about dysmenorrhe is important to have for each teenage girls and young adults. The goal of this study is knowing the picture of knowledge and attitude in facing dysmenorrhe on Faculty of Medicine Krida Wacana Christian University students batch 2019. With methods descriptive research involving 107 students of Faculty of Medicine Krida Wacana Christian University batch 2019 throughout October-November 2021. Data acquired by online questionnaire. As the results of the study showed that students of the Faculty of Medicine, Krida Wacana Christian University batch 2019 had a low level of knowledge of 42,1% , moderate 40,2%, and a high level of 18,8%. Meanwhile for attitude, the result were 51,4% good, 48,6% moderate. And 0% poor. The conclusion is majority of students of Faculty of Medicine Krida Wacana Christian University batch 2019 have low level of knowledge however have a good attitude in facing dysmenorrhe.